Children Positive Behaviour and the role of Interpersonal Communication in Family - Saragih, Nurhayani; Rossa, Ave; Theresia, Yohana (Universitas Mercu Buana, 2023)
This research is motivated by a decline in the intensity of face to face communication that exists within a family. The purpose of this study is to know the role of parent openness, parent empathy, parent support, positive sense of parent, parent position similarity in the formation of positive behavior of children. This study approach by using qualitive study with descprive method whice become subject in this research are family whose having many children and family whose having single child. In this study there are DeVito theories of interpersonal communication factors in shaping positve behavior of openess, empathy, positive sense, and similarity and as for positive behavior measured from the attitude of discipline, work hard honest, faithfull, responsible, tolerent, efficient, and be cautious to God Almighty. Researchers use post-positivism paradigm, in depth interview data collection techniques and literature study. The result of research of the role of communication beteween parints in the formation of positive behavior there are several factor – factors of openess, empathy, supportive attitude, positive attitude, and equality. This study concluded that the behavior of children can be formed positive the must be balanced with parent role. Where interpersonal communication is the most effective communications in the formation of positive behavior of children because communication as a tool for parenting and tools for the role model and interpersonal communication is well established in the family resulted in the formation of positive behavior of children.